2018
DOI: 10.1111/tid.12916
|View full text |Cite
|
Sign up to set email alerts
|

Late‐phase human herpesvirus 6B reactivation in hematopoietic stem cell transplant recipients

Abstract: Late-phase HHV-6B infection in HSCT recipients was associated with worse outcomes. The full spectrum of clinical features of the infection has not been fully elucidated, and therefore, recipients with high-risk factors for late-phase HHV-6B infection should be carefully monitored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…In support, the integrated HHV-6B genome is generally intact and conserved without any gross rearrangements or mutations [ 17 ]. Furthermore, the integrated HHV-6B genome can express genes and lead to complete viral reactivation [ 2 , 10 , 18 , 19 ]. Until now, viral or cellular proteins involved in HHV-6B integration remains to be fully characterized.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In support, the integrated HHV-6B genome is generally intact and conserved without any gross rearrangements or mutations [ 17 ]. Furthermore, the integrated HHV-6B genome can express genes and lead to complete viral reactivation [ 2 , 10 , 18 , 19 ]. Until now, viral or cellular proteins involved in HHV-6B integration remains to be fully characterized.…”
Section: Introductionmentioning
confidence: 99%
“…Following primary infection, HHV-6B enters in latency. In immunocompromised patients such as hematopoietic stem cell transplantation recipients, HHV-6B frequently reactivates from latency and can cause serious medical complications [2][3][4]. During latency, most herpesviruses maintain their genome as a circularized episome.…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon is referred to as inherited chromosomally integrated HHV-6 (iciHHV-6). Importantly, HHV-6 reactivation from the integrated state is associated with various diseases, including graft-versus-host disease, encephalitis, and heart disease (12)(13)(14)(15)(16)(17)(18). More recently, a study indicated that telomeres carrying integrated HHV-6 are shorter and more unstable (19), which, in turn, could influence aging and/or diseases of individuals with iciHHV-6.…”
mentioning
confidence: 99%
“…In healthy subjects, HHV-6B reactivation is mostly subclinical and controlled by the immune system. However, in immunocompromised individuals, HHV-6B reactivation can be problematic and occasionally life-threatening (5),(6),(7). In case of HHV-6A, several reports have associated the virus with neurodegenerative diseases such as multiple sclerosis and more recently with Alzheimer’s disease (8), (9), (10), (11).…”
Section: Introductionmentioning
confidence: 99%
“…In support, the integrated HHV-6A/B genomes are generally intact and conserved without any gross rearrangements or mutations (17). Furthermore, integrated HHV-6A/B genomes can express genes and lead to complete viral reactivation (18)(19),(20),(7). Reactivation of HHV-6A/B can be life threatening for immunocompromised hosts.…”
Section: Introductionmentioning
confidence: 99%